Trace element and calcareous nannofossil assemblage of the Smoky Hollow (SH#1) core in south central Utah - Victoria Fortiz; Rosie L Oakes; F Garrett Boudinot; Matthew M Jones; R Mark Leckie; Bradley B Sageman; Julio Sepúlveda; Timothy J Bralower (PANGAEA, 2021)
Trace element data from the Smoky Hollow #1 core drilled across the Cenomanian-Turonian boundary near Big Water, south-central Utah in 2014. Ground bulk samples were analyzed via Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) in the Laboratory for Isotopes and Metals in the Environment (LIME) at The Pennsylvania State University. Results are given with both raw (bulk) and normalized to Zr to correct for detrital input. The data include nannofossil assemblages from the Cenomanian-Turonian boundary of the Smoky Hollow (SH#1) core in south central Utah. For assemblage studies, slides were made from more dilute solutions so that counts could be conducted. Nannofossil specimens were observed under a Carl Zeiss Axioskop 2 Plus light microscope at a magnification of 1000x and identified using standard taxonomy as described by Perch-Nielsen et al. (1985). Specimens one-half the size of a coccolith or larger were identified and a total of over 31,000 specimens were counted.